(untitled) (Revista Inclusiones, 2020)
The purpose of this article is to consider the role of alternative consideration of disputes as an indicator of social democratization. This study is carried out using historical and comparative-legal methods. This article examines the importance of conciliation in civil and arbitration proceedings for society. The authors briefly examine the history of the emergence of alternative ways to dispute resolution, as well as the views of representatives of the scientific community on the essence of conciliation and its role in the judicial process. As a result, it is concluded that at present, out-ofcourt dispute resolution is a legal means of implementing and simplifying justice. The authors conclude that it is necessary to distinguish between the concepts of out-of-court and pre-court methods of dispute resolution. It is also concluded that Russian law is moving towards expanding the scope of alternative dispute resolution. The Russian practice of applying alternative procedures gradually includes other technologies of peaceful dispute resolution that are known in foreign countries, such as facilitation, communication procedure, etc. As a result, this direction of legislation development and its application should contribute to the strengthening of civil society.